Educación sexual para el desarrollo integral de los niños y las niñas del septimo año paralelo C de Educación General Básica en la Unidad Educativa Rafael Vásconez Gómez durante el año lectivo 2016-2017 - Loor Gende, Jessica Margarita (2017)
The present investigation covered the prior knowledge of sexuality in seventh year students of basic education, for it was proposed as a general objective to determine the levels of training in sexual aspects that allow the integral development of the children of seventh year parallel " C "of Basic General Education in the Educational Unit" Rafael Vásconez Gómez "during the academic year 2016-2017. It was based on a descriptive, deductive, bibliographical, quantitative and field research to address this social and formative problem, for which a survey was applied to the educational community, determining that the Educational Unit "Rafael Vásconez Gómez" has not incorporated in its Curricular mesh the subject of Sexual Education, for this reason also do not have the necessary didactic resources for teachers to teach classes on these topics; although the teachers in a daily way have cleared doubts and concerns in students and intervened even in sentimental issues that were presented among them, have not received the support of the parents, who even inviting them, the vast majority have not attended. The meetings of representatives, nor do they talk about sexual issues with their children, which has generated many intrinsic conflicts in young people. It was proposed as a solution to the problem identified, the development of a didactic guide in the area of sexuality, that contributes with the teaching work and facilitates the student learning in this matter, a situation that will allow students to accept and recognize themselves as sexual beings and the Instead of being responsible for their own actions, fostering in them the maturity, knowledge, care and respect for their body and that of others.